Dynamic range evaluation of the immitance logic elements - Филинюк, Николай Антонович; Лищинская, Людмила Брониславовна; Чехместрук, Роман Юриевич; Фурса, Светлана Евгенивна (Eastern-European Journal of Enterprise Technologies, 2014)
The parameters, characterizing dynamic range of immitance logic element (ILE) were substantiated in the paper. Since the dynamic ILE range evaluation has not been undertaken yet, the task to assess it was set. The methods for determining the noise factor, signal power, which allow to determine the ILE dynamic range, were considered. The dynamic range of the element “NOT’’ of R and LC types, based on bipolar transistor was investigated. The ILE dynamic range is determined by the dependence of the ILE output immittance on the signal power and ILE input noise level. For analytical evaluation of ILE dynamic range, the coefficient equal to the ratio of maximum signal power, at which the value of the converted immittance at the ILE output does not vary more than by 10 %, to the minimum ILE input noise power was proposed. Numerical dynamic range evaluation of immittance logic elements “NOT’’ of R- and LC-type, based on bipolar transistor showed that their dynamic range is equal to 92 and 110 dB respectively, and can be increased by narrowing the noise bandwidth. These results allow to use the ILE in modern technology